Shadow man a novel - Drew, Alan 1970- (New York Random House, 2017)
"Vice cop Ben Wade has returned to his hometown of Santa Ana for a quieter life. When a woman is murdered in her kitchen, the town finds itself at the mercy of a serial killer who slips through windows and screen doors, shattering illusions of safety. As Ben and forensic specialist Natasha Betencourt struggle to stay one step ahead of the serial, Ben's own world is rocked again by a teen's suicide. Ben must decide how far he is willing to go, and how much he will risk, to rescue the town from a long buried evil, as well as from a psychotic serial killer. With eerie, chilling, as well as fine prose, Alan Drew brings us into the treacherous underbelly of a suburban California town in this suspenseful novel of thrilling noir, the story of a community confronted with the heart of human darkness"--Provided by publisher.
Keywords: Serial murderers -- Fiction; Murder -- Investigation -- Fiction; Suspense fiction